(untitled) (Lantanida Journal, 2017)
That the learning outcomes is an overview of the progress or development of students from the first to follow the educational program until the time they ended the educational program which he passes. So the study results can be seen after learners gain experience learning and behavioral changes. So with a change in the student after a learning experience and that’s called learning outcomes. Someone students who have high motivation to learn, have the drive or desire to learn a subject, students who have the desire and drive to learn a subject guided by their needs. One needs are close to success in learning a subject is need for achievement. That students who have high motivation to learn, will be marked with a bold desire to compete and receive feedback and encouragement to always be responsible and goal attainment. That students who have the drive to take responsibility and achievement of learning objectives, makes the learners to always be disciplined and focused in learning a subject. Therefore, students who have high motivation to learn, will get better learning outcomes compared to students with low learning motivation. Thus, if in improving learning outcomes of a subject, the need for efforts to increase student motivation. Motivation is realized in the form of action, is one factor that can be used to predict the progress of learning.